2022
DOI: 10.3390/cancers14153629
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Identification of the RNA-Binding Protein STAU2 as a Key Regulator of Pancreatic Adenocarcinoma

Abstract: Pancreatic adenocarcinoma (PAAD) is a highly aggressive cancer. RNA-binding proteins (RBPs) regulate highly dynamic post-transcriptional processes and perform very important biological functions. Although over 1900 RBPs have been identified, most are considered markers of tumor progression, and further information on their general role in PAAD is not known. Here, we report a bioinformatics analysis that identified five hub RBPs and produced a high-value prognostic model based on The Cancer Genome Atlas (TCGA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Additionally, subsequent research has shown that modification of the bioenergetics of PC cells could effectively influence the functionality of TRIM29 through a collaborative effort facilitated by the recruitment of miR-2355-3p and DDX3X to the AK4 transcript [ 27 ]. Recently, a noteworthy finding has emerged, underscoring the indispensable regulatory role of STAU2 in pancreatic adenocarcinoma, and DDX3X was identified as its target gene [ 28 ]. In light of these discoveries, one hypothesis suggests that the upregulation of DDX3X is a contributing factor to the advancement and dissemination of pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, subsequent research has shown that modification of the bioenergetics of PC cells could effectively influence the functionality of TRIM29 through a collaborative effort facilitated by the recruitment of miR-2355-3p and DDX3X to the AK4 transcript [ 27 ]. Recently, a noteworthy finding has emerged, underscoring the indispensable regulatory role of STAU2 in pancreatic adenocarcinoma, and DDX3X was identified as its target gene [ 28 ]. In light of these discoveries, one hypothesis suggests that the upregulation of DDX3X is a contributing factor to the advancement and dissemination of pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Immune infiltration is pivotal in the tumor microenvironment and is closely related to tumor growth, metastasis, and treatment response [19]. PD-L1 is a crucial immune checkpoint, and its expression on tumor cells is associated with immune evasion and poor prognosis [20].…”
Section: Introductionmentioning
confidence: 99%